Are SGLT2 polymorphisms linked to diabetes mellitus and cardiovascular disease? Prospective study and meta-analysis - Drexel, Heinz (Biosci Rep, 2019)
Inhibition of the sodium glucose co-transporter 2 (SGLT2) reduces cardiovascular morbidity, and mortality in patients with type 2 diabetes mellitus (T2DM) with atherosclerotic, cardiovascular disease. So far, a link between common genetic variations of the SGLT2 encoding gene SLC5A2 and glucose homeostasis as well as cardiovascular disease has not been established. The present study, therefore, aimed to investigate SLC5A2 single nucleotide polymorphisms (SNPs) in relation to type 2 diabetes and coronary artery disease (CAD) and prospectively the incidence of cardiovascular events. We genotyped the SLC5A2 tagging SNPs rs9934336, rs3813008, and rs3116150 in a total of 1684 high risk cardiovascular patients undergoing coronary angiography, including 400 patients with T2DM. Additionally, we performed a meta-analysis combining results from the present study and the literature. Variant rs9934336 was significantly associated with decreased HbA1c (P = 0.023). Further, rs9934336 was significantly inversely associated with the presence of T2DM in univariate (OR = 0.82 [0.68–0.99]; P = 0.037) as well as in multivariate analysis (OR = 0.79 [0.65–0.97]; P = 0.023). The association between rs9934336 and T2DM was confirmed in a meta-analysis including results from two previous observations which by themselves had failed to show a significant association of the polymorphism with T2DM (OR = 0.86 [0.78–0.95]; P = 0.004). Polymorphisms rs3813008 and rs3116150 were associated neither with glycemic parameters nor with T2DM. None of the SNPs tested was significantly associated with the baseline presence of CAD or the incidence of cardiovascular events. We conclude that genetic variation within the SLC5A2 gene locus is significantly related to the manifestation of T2DM.